2011
DOI: 10.1021/jo102374z
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Access to Halohydrofurans via Brønsted Acid-Catalyzed Hydroxylation/Halocyclization of Cyclopropyl Methanols with Water and Electrophilic Halides

Abstract: A one-pot, two-step method to prepare 3-halohydrofurans efficiently by TfOH-catalyzed hydroxylation/halocyclization of cyclopropyl methanols with H(2)O and N-halosuccinimide (NXS, X=1, Br, Cl) or Selectfluor is described. The reactions proceed rapidly under mild and operationally straightforward conditions with a catalyst loading as low as 1 mol % and afford the 3-halohydrofuran products in moderate to excellent yields and, in most cases, with preferential cis diastereoselectivity. The method was shown to be a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(15 citation statements)
references
References 81 publications
0
15
0
Order By: Relevance
“…More recently, Chan and co-workers reported a TfOH-catalyzed one-pot, two-step synthetic method for the preparation of 3-halohydrofurans 142 from cyclopropylmethyl alcohols 139 (Scheme 1.46). 91 The reaction was shown to be efficient for a variety of cyclopropyl alcohols in the presence of TfOH at a low catalyst loading of 1 mol%. After hydroxylation, halocyclization of the resultant homoallylic alcohols 141 formed in situ with NIS gave the desired substituted 3-iodofurans 142 were obtained in up to 98% yield and with complete cis selectivity.…”
Section: Scheme 143 Yb(otf) 3 Catalyzed Amination Of Cyclopropylmethmentioning
confidence: 99%
“…More recently, Chan and co-workers reported a TfOH-catalyzed one-pot, two-step synthetic method for the preparation of 3-halohydrofurans 142 from cyclopropylmethyl alcohols 139 (Scheme 1.46). 91 The reaction was shown to be efficient for a variety of cyclopropyl alcohols in the presence of TfOH at a low catalyst loading of 1 mol%. After hydroxylation, halocyclization of the resultant homoallylic alcohols 141 formed in situ with NIS gave the desired substituted 3-iodofurans 142 were obtained in up to 98% yield and with complete cis selectivity.…”
Section: Scheme 143 Yb(otf) 3 Catalyzed Amination Of Cyclopropylmethmentioning
confidence: 99%
“…Cyclopropyl‐substituted radicals 6 (Scheme c) may ring‐open to form alkenes, but carbocation 5 may also have this tendency (vide infra). As exemplified in Scheme c, ene‐ynes 7 can form through rearrangement if a cyclopropyl‐substituted propargylic alcohol 4 is employed . The employment of cyclopropyl‐substituted propargylic alcohols in reactions with alcohols to give conjugated, achiral enynes has been reported previously only four times, utilizing Yb(OTf) 3 ,[36a] triflic acid (TfOH),[36b] HAuCl 4 [36c] and ruthenium complexes[36d] as catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Lewis and Brønsted acid-catalyzed reactions of unsaturated alcohols have emerged over the years as efficient and convenient synthetic strategies for C À C and C À X (X= N, O, S) bond formation. [4][5][6] For example, we recently reported a method for the synthesis of indenyl-fused and 2,3-disubstituted indoles that relied on the cycloisomerization of 2-tosylaminophenylprop-1-yn-3-ols in the presence of a gold(I) catalyst. [2b] We subsequently demonstrated that the synthetic method could be fine-tuned to provide 1H-indole-2-carbaldehydes and (E)-2-(iodomethylene)indolin-3-ols by introducing N-iodosuccinimide into the reaction conditions.…”
mentioning
confidence: 99%